1976
DOI: 10.1007/bf00428979
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose tissue in culture V. Studies on the metabolic effects of insulin

Abstract: Summary.Specimens of human adipose tissue were cultured for one week with or without the addition of insulin. The basal as well as the noradrenaline-stimulated lipolysis were enhanced in the explants cultured with insulin, showing that the long-term effect of the hormone is lipolytic. However, an acute antilipolytic effect of insulin could be demonstrated in these explants in the subsequent short-term incubations. The basal rate of glucose incorporation into the lipids was enhanced in the explants cultured wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Resorption rates between 30% and 60% have been reported in the literature. 15,26 In our study, we observed that 90% of our patients have 40-50% of fat resorption, which is consistent with the above studies. Some authors have reported success rate with needle transplantation of fat from 0% to 100%.…”
Section: Fat Survival Theoriessupporting
confidence: 91%
“…Resorption rates between 30% and 60% have been reported in the literature. 15,26 In our study, we observed that 90% of our patients have 40-50% of fat resorption, which is consistent with the above studies. Some authors have reported success rate with needle transplantation of fat from 0% to 100%.…”
Section: Fat Survival Theoriessupporting
confidence: 91%
“…Thus, when maintained in culture in the absence of exogenous hormones, pyruvate kinase activity declines in rat hepatocytes (Miyanaga et at., 1982(Miyanaga et at., , 1983Evans et al, 1984;Fleig et al, 1984), whereas it increases in adipose tissue from man (Smith et al, 1976) and cattle (Vernon et al, 1985). In addition, although glucocorticoids act in concert with insulin to maintain pyruvate kinase in rat hepatocytes maintained in culture (Feliu et al, 1982;Miyanaga et al, 1982Miyanaga et al, , 1983Evans et al, 1984;Fleig et al, 1984), we now show that they antagonize the effects of insulin on the enzyme activity in sheep adipose tissue.…”
Section: Pyruvate Kinasementioning
confidence: 42%
“…When adipose tissue from sheep was maintained in tissue culture for 24 h, the rate of glucose utilization increased; this was accompanied by an increase in pyruvate kinase activity, whereas the activity of a number of other enzymes, including hexokinase and phosphofructokinase, did not change (Robertson et al, 1982). A selective increase in pyruvate kinase activity has also been observed when human adipose tissue is maintained in tissue culture (Smith et al, 1976). In contrast with its lack of effects during short-term incubations, insulin stimulated glucose uptake and also increased pyruvate kinase activity of bovine adipose tissue during incubations for 24 h or longer (Vernon et al, 1985).…”
Section: Introductionmentioning
confidence: 86%
“…The biopsies were cleaned of blood and tissue debris, dissected into 10-20 mg biopsies and incubated in medium 199 containing 4% human albumin, 25 mM HEPES, and 5.6 mM glucose according to previously reported procedures. 11,12 The biopsy procedure was approved by the Ethical Committee of Göteborg University. Biopsies were cultured with or without 20 ng/ml TNFa for 24 h.…”
Section: Methodsmentioning
confidence: 99%